Systemic glucocorticoid and anti-tuberculosis therapy in a patient with coexisting tuberculosis and anthracosis - Tutluer, Seda; Tanriover, M. D.; Emri, S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: Tuberculous lymphadenitis is a common condition in underdeveloped and developing countries. Anthracosis is the black pigmentation of bronchi caused by the deposition of carbon, silica and quartz particles in the macrophages of the bronchial mucosa and submucosa. There is a potential relationship between bronchial anthracofibrosis and tuberculosis (TB). Objectives: A 66 year old woman was referred to a chest diseases clinic when non-productive cough was noticed during a preoperative examination. Computerized tomography (CT) of thorax showed an infiltration in the right upper lobe and a lesion in the right apical lobe adjacent to the trachea. Extensive diagnostic tests including mediastinoscopic lymph node excision were performed. Anthracosis and coexisting tuberculosis were diagnosed.Results: Directly observed anti-TB therapy was immediately initiated. Systemic prednisolone was initiated at a dose of 30 mg/day and tapered slowly to the maintenance dose. Control thorax CT taken two months after the initiation of therapy revealed that the right upper lobe bronchus was open and atelectasis of the right upper lobe was resolved. Mediastinal calcified lymph nodes and fibrotic changes of both apical regions were observed. Being in the 10th month of the therapy, the patient is still totally asymptomatic in follow-ups. Conclusions: Glucocorticoid therapy may raise some concerns in patients with TB. Here, we present a case with anthracosis and coexistent TB, who responded very well to simultaneous anti-TB and glucocorticoid therapy.